Squalenyl Hydrogen Sulfate Nanoparticles for Simultaneous Delivery of Tobramycin and an Alkylquinolone Quorum Sensing Inhibitor Enable the Eradication of P. aeruginosa Biofilm Infections. (11th May 2020) - Ho, Duy‐Khiet; Murgia, Xabier; De Rossi, Chiara; Christmann, Rebekka; Hüfner de Mello Martins, Antonio G.; Koch, Marcus; Andreas, Anastasia; Herrmann, Jennifer; Müller, Rolf; Empting, Martin; Hartmann, Rolf W.; Desmaele, Didier; et al.
Abstract: Elimination of pulmonary Pseudomonas aeruginosa (PA) infections is challenging to accomplish with antibiotic therapies, mainly due to resistance mechanisms. Quorum sensing inhibitors (QSIs) interfering with biofilm formation can thus complement antibiotics. For simultaneous and improved delivery of both active agents to the infection sites, self‐assembling nanoparticles of a newly synthesized squalenyl hydrogen sulfate (SqNPs) were prepared. These nanocarriers allowed for remarkably high loading capacities of hydrophilic antibiotic tobramycin (Tob) and a novel lipophilic QSI at 30 % and circa 10 %, respectively. The drug‐loaded SqNPs showed improved biofilm penetration and enhanced efficacy in relevant biological barriers (mucin/human tracheal mucus, biofilm), leading to complete eradication of PA biofilms at circa 16‐fold lower Tob concentration than Tob alone. This study offers a viable therapy optimization and invigorates the research and development of QSIs for clinical use. Abstract : Breaking through : Tob and QSI (1) co‐loaded squalenyl hydrogen sulfate nanoparticles (SqNPs) are shown to act on all stages of P. aeruginosa infections to eradicate bacterial infection [(a–c) and (e)] and penetrate biofilm, preventing its formation and recurrence (d).